Establishing Program Educational Objectives - Shivakumar, R.; Usha, H. S.; Nayak, Chetan A.; Sainath, K.; Maitra, Samita (Journal of Engineering Education Transformations, 2015)
Outcome based education establishes a method of evaluating the program education objective. The National board of Accreditation, India has laid down 12 attributes as program outcomes which suits the engineering education as per the norms of ABET accreditation system globally. The attainment of these 12 attributes as program objective will have to be mapped to the Program Educational Objective (PEO). The attainment of the program outcomes is achieved by designing the curriculum considering all the attributes so that the graduate gets trained in all the outcomes. The attainments of the PEOs are assessed by alumni, employees, graduate entrepreneurs and stake holders’ survey.